Components of Social Media Marketing Capabilities That Support The Marketing Performance of Micro Small to Medium Enterprises (MSMEs) - Herman, Ferey; Budianto, Apri; Enas, (Jurnal Manajemen (Edisi Elektronik), 2023)
This paper aims to understand the importance of marketing capabilities in using social media on business performance. The conceptualization was developed based on Morgan’s marketing capabilities framework. Data was collected from SMEs in the food sector who just received a certificate for food safety, which means they have had the opportunity to market their product widely. Partial least squares structural equation modelling will be used to analyze data. The results of this study will have some limitations/implications: First: The data was collected using a non-probability sampling method, commonly known as convenience sampling. Second: Perceptual measures used on performance variables in this analysis. Third: This study neglects data changes from time to time, in other words, this study obtains cross-sectional data collection. Finally, the study was only conducted in Tasikmalaya’s food sector and therefore does not lend itself to any general applicability. The originality of this study lies in the fact that this research is the first research that provides a complete view of social media applications in supporting SMEs in the food sector marketing performance.